A Parametric Study of SOFC Performances with Multi-Stage Electrochemical Oxidation for Enhancement of Electric Efficiency. (2nd June 2015) - Matsuzaki, Yoshio; Tachikawa, Yuya; Hatae, Toru; Matsumoto, Hiroshige; Taniguchi, Shunsuke; Sasaki, Kazunari
Abstract : The solid-state ceramic construction of SOFCs enables high fuel to electricity conversion efficiencies of as high as 50 to 60 percent LHV in high temperature operation, and allows more flexibility in fuel choice. In this study, we have developed a symbolic analysis method to investigate the availability of variable parameters appeared in multi-stage electrochemical oxidation mechanism that is expected to further improve the electric efficiencies of SOFCs. In the flow system of the multi-stage oxidation, the fuel utilization, Uf, at the most downstream stack, Uf M, is expressed as a function of number of stacks, n, and total fuel utilization, Uf T . When n = 10 and Uf T = 85%, Uf M is calculated to be 36%, which is much smaller than Uf T . Therefore, if the most downstream stack has high robustness against lean fuel gas, Uf T could be set to be higher values without serious degradation by using this flow system.